Formulasi dan Evaluasi Sediaan Lipstik Ekstrak Bunga Kembang Sepatu (Hibiscus rosa-sinensis L.) Sebagai Pewarna Alami - Safriana Safriana; Tri Susanti Sirait; Aida Apriani; Yunda Fachrunniza; Muhammad Rizki (Journal of Pharmaceutical and Sciences, 2026)
Synthetic dyes in decorative cosmetics remain a safety concern when prohibited colourants are used in products that are applied repeatedly to the lips. Hibiscus flower (Hibiscus rosa-sinensis L.) contains anthocyanins that can provide red to purple hues. This preliminary laboratory study prepared solid lipsticks containing 0%, 3%, 6%, 9%, and 12% hibiscus flower extract and evaluated organoleptic characteristics, approximate pH, short-term room-temperature stability, acute irritation response, and descriptive consumer preference. Dried flower powder underwent two-stage maceration with citric-acidified 96% ethanol, and the concentrated extract was incorporated into a wax-lipid base. The sticks weighed 3- 3.5 g and were easy to apply. The extract-free formula was colourless, while extract-containing formulas produced bright pink to dark red shades. No visible changes in shape, colour, or odour were observed during 30 days of room-temperature storage. All formulas showed an approximate pH of 5 by indicator paper and caused no redness, itching, or oedema in 10 volunteers during a 30-minute preliminary acute irritation screening. The 12% formula had the highest aggregate hedonic score, but statistical superiority could not be determined because panellist-level raw data were unavailable. These findings provide preliminary formulation evidence. Interpretation remains limited by non-identical base compositions, visual colour assessment, non-instrumental pH measurement, and the absence of anthocyanin quantification and accelerated stability testing.